2014
DOI: 10.1016/j.biomaterials.2014.05.084
|View full text |Cite
|
Sign up to set email alerts
|

The roles of blood-derived macrophages and resident microglia in the neuroinflammatory response to implanted Intracortical microelectrodes

Abstract: Resident microglia and blood-borne macrophages have both been implicated to play a dominant role in mediating the neuroinflammatory response affecting implanted intracortical microelectrodes. However, the distinction between each cell type has not been demonstrated due to a lack of discriminating cellular markers. Understanding the subtle differences of each cell population in mediating neuroinflammation can aid in determining the appropriate therapeutic approaches to improve microelectrode performance. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 68 publications
4
92
0
Order By: Relevance
“…Since acrolein is produced as a result of mechanical damage to the CNS, particularly neural tissue, 35,50,67 it is likely that the mechanical stresses and strains responsible for damaging the BBB also traumatically deform local neural tissue, resulting in consequential elevation of acrolein. Because acrolein can also independently cause cellular damage, 48,50,61 including damage to lipid membranes, 48,67,74 it is likely that acrolein elevation further worsens BBB integrity. In summary, the BBB damage is consistent with and suggests that upregulation of acrolein occurs as a result of direct mechanical damage to brain tissue resulting from BINT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since acrolein is produced as a result of mechanical damage to the CNS, particularly neural tissue, 35,50,67 it is likely that the mechanical stresses and strains responsible for damaging the BBB also traumatically deform local neural tissue, resulting in consequential elevation of acrolein. Because acrolein can also independently cause cellular damage, 48,50,61 including damage to lipid membranes, 48,67,74 it is likely that acrolein elevation further worsens BBB integrity. In summary, the BBB damage is consistent with and suggests that upregulation of acrolein occurs as a result of direct mechanical damage to brain tissue resulting from BINT.…”
Section: Discussionmentioning
confidence: 99%
“…63 While we cannot directly distinguish between the 2 cell types, peripheral macrophage infiltration has also recently been shown to correlate with neuronal death after mechanical disruption of the BBB. 61 Alterations in inflammatory cell density and morphology serve as further confirmation of damaged tissue and provide avenues for further investigation. With acrolein’s known ability to initiate and perpetuate proinflammatory pathways, specifically from the macrophage lineages, 4,12,30,40,59 it is possible that sequestration of acrolein will mitigate this upregulation of inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to support this hypothesis has been limited to finite element simulation studies (6, 7) and in vivo studies which rely on histological analysis (8, 3033). These studies highlight the importance mechanical effects at the tissue-implant interface, but are also confounded by the presence of other factors that are present when using in vivo models including damage from surgical implantation (34), blood-brain barrier breach (9), and the presence of blood-derived macrophages (35). All of these components are likely to play a role in the scar formation process.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies suggested that greater microglia attachment was correlated with more hydrophobic materials tested. Extending this work, Ravikumar et al [131], used chimeric mice, with cyan fluorescent protein (CFP) modified blood monocyte/macrophage cells, so that the relative populations of peripheral macrophages (CFP þ /IBA1 þ ) and microglia (CFP À /IBA1 þ ) could be tracked histologically after implantation of a microdevice. At each time point studied, more than 60% of the activated immune cells were macrophages, with the implication that neuronal dieback in vivo correlated more with increases in macrophage populations and not microglia.…”
Section: Monocyte/macrophage Culturesmentioning
confidence: 98%